Rancangan Sistem Monitoring Dan Reminder Absensi Kehadiran dengan Menggunakan Fingerprint Berbasis SMS Gateway di Prodi TNU Politeknik Penerbangan Surabaya - Ivando Bayhaqi; Romma Diana P; Dhian Supardam (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Monitoring the presence of both lecturers and midshipmen is important to realize the academy aspirations to creategraduates who are competent in the field of aviation. And upgrade to administrative process validation.Therefore, to be able to make the equipment can work automatically and reduce the excessive use of paper. By usingFingerprint Sensor Machine.